THE IMPLEMENTATION OF THEME-BASED TEACHING WITH SHORT STORY TO IMPROVE STUDENTS’ READING COMPREHENSION THE TENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 1 PALEMBANG - Dessy Novitha; Retika Wista Anggraini (Universitas Indo Global Mandiri, 2018)
This study was aimed to observe the use of Theme-Based Teaching with short story, and to find out the obstacles, advantages and disadvantages of theme based teaching using short story and narrative text. This study was conducted by using a quasi-experimental design with pretest and posttest. The population of this study consisted of 259 tenth grade students of SMA Muhammadiyah 1 Palembang in Academic Year of 2016/2017. There were 40 students taken as sample. Each group consisted of 20 students as experimental group and 20 students from class as control group. The sample of this study was taken by using purposive sampling method. In this study, the researcher used pretest-posttest non-equivalent group design. The instrument used in collecting the data was oral test in the form of presentation. The test was administrated twice as the pretest and posttest for both experimental and control group. The results of the test were analyzed by using IBM SPSS (Statistical Package for the Social Science) Statistics 21. The result showed that “there was means significant difference from students posttest score in experimental and control group, it was found the p-ouput (Sig.2-tailed) was lower than 0.05 level and t-obtained (9.823) is higher than t-table (2.024). So, the Ho (the null hypothesis) was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ reading comprehension achievement taught using Theme-Based Teaching than students who were taught by using teacher’s strategy. The findings of this study suggested that Theme based teaching was effective in improving students’ reading comprehension on narrative text as indicated by a statistically higher reading score of experimental group students.Key word : theme-based teaching, reading achievement